2015
DOI: 10.1111/jocn.12888
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of needs related to the practice of self‐care for minor illness

Abstract: Aims and objectives. The aim of this study was to describe people's perceptions of needs to feel confident in self-care for minor illnesses as well as their perceptions about supporting and obstructing factors in the practice of self-care. Background. Minor illness constitutes a large part of primary care, and patients' attendance to doctors' appointments for minor illness has been seen to increase future attendance for the same condition. Almost half of the consultations with telenurses result in the provisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 29 publications
(37 reference statements)
0
16
1
Order By: Relevance
“…Knowledge about how to obtain symptom relief is needed to feel confident in the practice of self‐care (Gustafsson et al . ), and knowledge about minor illnesses is built up through experiencing minor illnesses (Gustafsson et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Knowledge about how to obtain symptom relief is needed to feel confident in the practice of self‐care (Gustafsson et al . ), and knowledge about minor illnesses is built up through experiencing minor illnesses (Gustafsson et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…However, younger callers in our study were significantly less satisfied to feel confident in their practice of self-care, and young persons have been found to have a greater need to have someone with whom they can discuss minor illness. Knowledge about how to obtain symptom relief is needed to feel confident in the practice of self-care (Gustafsson et al 2015b), and knowledge about minor illnesses is built up through experiencing minor illnesses (Gustafsson et al 2015a). It could be that younger persons lack the experience and have unmet needs related to dealing with minor illness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-care can also be seen as a personal learning process to manage health concerns (14). Receiving advice and reliable information for minor health concerns can create a feeling of confidence in selfcare (48). However, it has been shown that self-care ability decreases with increasing age and when home care is provided (16).…”
Section: Discussionmentioning
confidence: 99%
“…Active surveillance can be described as a treatment strategy that involves closely watching a patient's condition but not giving any treatment unless the condition is getting worse. Minor illness is defined as conditions that require little or none medical intervention and that cause a disruption in people's everyday life during a short period of time (Gustafsson, Vikman, Sävenstedt, & Martinsson, ). The management strategy for minor illnesses is important because care‐seekers tend to take on strategies from past experiences.…”
Section: Introductionmentioning
confidence: 99%